"When our membership awakens": Welfare Work and Canadian Union Activism, 1950-1965 - Tillotson, Shirley (Labour / Le Travail, 1997)
Rather than seeing the mainstream, anti-communist labour leadership in the post-war era as opponents of membership activism and as politically right wing, we might more accurately see them as ideologically-diverse architects of an activism designed to suit the institutional conditions of the new industrial legality in the Cold War era. Labour bureaucrats they indisputably were, but the new regime of industrial relations prompted them to re-examine and to attempt to democratize the basis of their institutional power. Evidence for this thesis is supplied through a study of welfare work and its promoters. Further evidence lies in a survey of idological interpretations of union welfare work and the political uses to which it was put.
Keywords: Anti-communist movements; COLD War, 1945-1989; Civil service; INDUSTRIAL welfare; LABOR laws & legislation; Labor leaders; Social movements